2021
DOI: 10.3389/fcell.2021.759820
|View full text |Cite
|
Sign up to set email alerts
|

Coiled-Coil Domain Containing 80 Suppresses Nonylphenol-Induced Colorectal Cancer Cell Proliferation by Inhibiting the Activation of ERK1/2

Abstract: Recently, the effect of endocrine-disrupting chemicals on the cancer procession has been a concern. Nonylphenol (NP) is a common environmental estrogen that has been shown to enhance the proliferation of colorectal cancer (CRC) cells in our previous studies; however, the underlying mechanism remains unclear. In this study, we confirmed the increased concentration of NP in the serum of patients with CRC. RNA sequencing was used to explore the differentially expressed genes after NP exposure. We found 16 upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In addition, we found that the expression of RGCC in tumor tissues is positively correlated with the concentration of NP in patients’ serum (Figure H). The tumor tissue sample from our previous study also demonstrated that NP treatment could increase RGCC expression in vivo (Figure I).…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…In addition, we found that the expression of RGCC in tumor tissues is positively correlated with the concentration of NP in patients’ serum (Figure H). The tumor tissue sample from our previous study also demonstrated that NP treatment could increase RGCC expression in vivo (Figure I).…”
Section: Resultsmentioning
confidence: 62%
“…The protein expression of the treated cells was analyzed using western blotting, as previously described. , The primary antibodies used were anti-E-cadherin (ab40772, Abcam,1:800), anti-N-cadherin (ab76011, Abcam,1:800), anti-vimentin (ab92547, Abcam,1:800), anti-ERK (ab184699, Abcam,1:800), anti-p-ERK (ab201015, Abcam,1:800), anti-RGCC (ab221098, Abcam,1:1000), and anti-GAPDH (5174, Cell Signaling Technology, 1:10 000). The IOD was analyzed using Image-Pro Plus 6.0 software (Media Cybernetics, MD).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of CCDC80 has been controversial in cancer research. Previous research indicated that the presence or high expression of CCDC80 might act as a protective factor in tumorigenesis. Recent studies have reported that CCDC80 inactivation promotes AOM/DSS-induced colorectal carcinogenesis in mice . However, other studies have shown that CCDC80 may act as a prognostic stemness biomarker in CRC and that high expression of CCDC80 contributes to drug resistance and tumor immune evasion .…”
Section: Discussionmentioning
confidence: 99%